MTOR inhibitors reduce enteropathy, intestinal bleeding and colectomy rate in patients with juvenile polyposis of infancy with PTEN-BMPR1A deletion. Issue 14 (2nd April 2021) - Taylor, Henry; Yerlioglu, Dilay; Phen, Claudia; Ballauff, Antje; Nedelkopoulou, Natalia; Spier, Isabel; Loverdos, Inés; Busoni, Veronica B; Heise, Jürgen; Dale, Peter; de Meij, Tim; Sweet, Kevin; et al.
Abstract: Ultra-rare genetic disorders can provide proof of concept for efficacy of targeted therapeutics and reveal pathogenic mechanisms relevant to more common conditions. Juvenile polyposis of infancy (JPI) is caused by microdeletions in chromosome 10 that result in haploinsufficiency of two tumor suppressor genes: phosphatase and tensin homolog deleted on chromosome 10 ( PTEN ) and bone morphogenetic protein receptor type IA ( BMPR1A ). Loss of PTEN and BMPR1A results in a much more severe phenotype than deletion of either gene alone, with infantile onset pan-enteric polyposis and a high mortality rate. No effective pharmacological therapy exists. A multi-center cohort analysis was performed to characterize phenotype and investigate the therapeutic effect of mammalian target of rapamycin (mTOR) inhibition (adverse events, disease progression, time to colectomy and mortality) in patients with JPI. Among 25 JPI patients identified (mean age of onset 13 months), seven received mTOR inhibitors (everolimus, n  = 2; or sirolimus, n  = 5). Treatment with an mTOR inhibitor reduced the risk of colectomy (hazard ratio = 0.27, 95% confidence interval = 0.07–0.954, P  = 0.042) and resulted in significant improvements in the serum albumin level (mean increase = 16.3 g/l, P  = 0.0003) and hemoglobin (mean increase = 2.68 g/dl, P  = 0.0077). Long-term mTOR inhibitor treatment was well tolerated over an accumulated follow-up time of 29.8 patient years. No serious adverse events were reported. Early therapy with mTOR inhibitors offers effective, pathway-specific and personalized treatment for patients with JPI. Inhibition of the phosphoinositol-3-kinase–AKT–mTOR pathway mitigates the detrimental synergistic effects of combined PTEN–BMPR1A deletion. This is the first effective pharmacological treatment identified for a hamartomatous polyposis syndrome. Graphical Abstract: